Bio-deposition approaches for sustainable execution of recycled aggregates in concretes - Ahmad, Muhammad Arslan; Liu, Bing; Li, Qiuwei; Adeel, Muhammad; Zhang, Jinlong; Zhou, Yingwu; Deng, Xu (Frontiers in Materials, 2023)
Our study offers a quantitative framework for microbial-induced calcium carbonate precipitation (MICP) to uplift the properties of recycled aggregate concrete (RAC). In this regard, a marine alkalophilic bacterium Bacillus sp. B6 was employed, and its growth and mineralization efficiency under seawater conditions was investigated. Optimization of MICP was achieved with different nutrient sources and bacterial introduction methods (dip and spray). The efficiency of treated recycled aggregates (RA) was determined by using scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) in combination with basic technologies of density improvement and water absorption. The results show that the optimal nutrient sources of carbon and nitrogen are glucose (7 gL-1) and tryptone (5 gL-1), respectively. Spray treated recycled aggregate (RA) is reported to be efficient with reduction in water absorption (~19%), improvement in bulk (~2.4%), and apparent density (~1.7%). The effectiveness of MICP treatment process is confirmed with SEM and EDX observations, indicating filling of microcracks with calcium carbonates. As such, the mechanical properties of RAC with spray treated RA significantly increase upto ~24% in compressive strength as compared to the control treatment. Current findings will help revitalize the construction industry by utilizing the MICP-treated RA and minimizing the load on natural aggregates.